HIV serodiscordant couples: can we have a baby? - Tin, Myo Han; Tin Tin , Hla (2014)

(untitled)
Women’s health involves women’s emotional, social, cultural, spiritual and physical well-being, and is determined by the social, political, cultural and economic context of women’s lives, as well as by biology. Illness presentation by gender, social determinants of women health, disease prevention/health promotion for common women health problems, reproductive health, women’ mental health, passages lifecycle issues at any age, cultural diversity/international women’s health, violence against women, advocate for individual women patients and the women’s health community and research in women’s health are themes which should be learned as family medicine specialists to provide comprehensive women health care . In this symposium, experiences of five lady family physicians on selected common women health issues in Myanmar will share with the conference audiences from the point of view of clinical practices guidelines, psycho-social-mental care by family medicine specialists, timely referral and coordinated care with other specialties. Titles and speakers as follows: 1.“Diabetes women and Pregnancy Care in GPs clinics” by Dr Tin Tin Hla 2.“How to deal with heavy menstrual bleeding patients in GPs clinics” by Dr Lwin May Oo 3.“Hormonal replacement therapy for post-menopausal women in GPs clinics” by Dr Daw Myint Myint 4.“Evening Primrose Oil! Is an alternative medicine for women health?” by Dr Aye Aye Thein 5. “ HIV Serodiscordant Couples : Can we have a baby ?” by Dr Tin Myo Han